Case report: Cardiac metastatic uterine intravenous leiomyomatosis excision with extracorporeal venous shunt under the guidance of 3-dimensional printing - Chen, Hong; Mao, Yu; Xie, Hongtao; Liu, Dejun; Zhang, Shun; Tian, Yongcang; Yang, Jian; Bai, Benjian (Frontiers in Cardiovascular Medicine, 2023)
Intravenous leiomyomatosis (IVL) is relatively rare, and the incidence of cardiac IVL is even lower. The case report introduces a 48-year-old woman with two episodes of syncope in 2021. Echocardiography showed a cord-like mass in the inferior vena cava (IVC), right atrium (RA), right ventricle (RV) and pulmonary artery. Computed tomography venography and magnetic resonance imaging showed strips in RA, RV, IVC, right common iliac vein, and internal iliac vein, as well as a round-like mass in the right uterine adnexa. Combined with the patient's prior surgical history and rare anatomical structures, surgeons used cardiovascular 3-dimensional (3D) printing technology to create patient-specific preoperative 3D printed model. The model could help surgeons to visually and accurately understand the size of IVL and its relationship to adjacent tissues. Finally, surgeons successfully performed a concurrent transabdominal resection of cardiac metastatic IVL and adnexal hysterectomy with off-cardiopulmonary bypass. Preoperative evaluation and guidance of 3D printing may play a critical role to ensure this surgery for the patient with rare anatomical structures and high surgical risk. Clinical Trial Registration: [ClinicalTrials.gov], Protocol Registration System [NCT02917980].